The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3892/ol.2013.1143
|View full text |Cite
|
Sign up to set email alerts
|

Small antibody fusion proteins with complementarity-determining regions and lidamycin for tumor targeting therapy

Abstract: Gelatinases are overexpressed in several types of maligancies and tumor stromal cells. Lidamycin is an enediyne antitumor antibiotic, which is composed of an apoprotein (LDP) and an active chromophore (AE). It is known that the heavy-chain complementarity-determining region-3 (CDR3) domain of scFv is important in antibody affinity. The aim of this study was to prepare the enediyne-energized fusion proteins with a heavy-chain CDR3 domain of anti-gelatinases scFv and lidamycin, and to evaluate their antitumor ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Though, LDM is a potent ''warhead'' drug, it lacks the targeting function resulting in systemic toxicity. Previous studies have shown that LDM-related enediyneenergized fusion proteins presented stronger inhibitory activity in tumor targeting therapy [36][37][38]. In this study, we conjugated the anti-CD19(Fab) antibody with LDM by genetic engineering to generate ADC anti-CD19(Fab)-LDM, which has a stable structure and delivers drug to the target cells.…”
Section: Discussionmentioning
confidence: 99%
“…Though, LDM is a potent ''warhead'' drug, it lacks the targeting function resulting in systemic toxicity. Previous studies have shown that LDM-related enediyneenergized fusion proteins presented stronger inhibitory activity in tumor targeting therapy [36][37][38]. In this study, we conjugated the anti-CD19(Fab) antibody with LDM by genetic engineering to generate ADC anti-CD19(Fab)-LDM, which has a stable structure and delivers drug to the target cells.…”
Section: Discussionmentioning
confidence: 99%